Leucine Modulates Mitochondrial Biogenesis and SIRT1-AMPK Signaling in C2C12 Myotubes - Chunzi Liang; Benjamin J. Curry; Patricia L. Brown; Michael B. Zemel (Journal of Nutrition and Metabolism)
Previous studies from this laboratory demonstrate that dietary leucine protects against high fat diet-induced mitochondrial impairments and stimulates mitochondrial biogenesis and energy partitioning from adipocytes to muscle cells through SIRT1-mediated mechanisms. Moreover, β-hydroxy-β-methyl butyrate (HMB), a metabolite of leucine, has been reported to activate AMPK synergistically with resveratrol in C2C12 myotubes. Therefore, we hypothesize that leucine-induced activation of SIRT1 and AMPK is the central event that links the upregulated mitochondrial biogenesis and fatty acid oxidation in skeletal muscle. Thus, C2C12 myotubes were treated with leucine (0.5 mM), alanine (0.5 mM), valine (0.5 mM), EX527 (SIRT1 inhibitor, 25 μM), and Compound C (AMPK inhibitor, 25 μM) alone or in combination to determine the roles of AMPK and SIRT1 in leucine-modulation of energy metabolism. Leucine significantly increased mitochondrial content, mitochondrial biogenesis-related genes expression, fatty acid oxidation, SIRT1 activity and gene expression, and AMPK phosphorylation in C2C12 myotubes compared to the controls, while EX527 and Compound C markedly attenuated these effects. Furthermore, leucine treatment for 24 hours resulted in time-dependent increases in cellular NAD+, SIRT1 activity, and p-AMPK level, with SIRT1 activation preceding that of AMPK, indicating that leucine activation of SIRT1, rather than AMPK, is the primary event.